2010
DOI: 10.1097/ccm.0b013e3181fa057f
|View full text |Cite
|
Sign up to set email alerts
|

Results of a survey of blood pressure monitoring by intensivists in critically ill patients: A preliminary study

Abstract: The use of noninvasive blood pressure measurement measurements in critically ill patients is common despite the paucity of evidence validating its accuracy in critically ill patients. Given this widespread use, accuracy and precision validation studies comparing noninvasive blood pressure measurement with intra-arterial blood pressure measurement in critically ill patients should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…There is, however, ample evidence suggesting that non-invasively measured MAP is a better indicator of invasive blood pressure than non-invasive systolic blood pressure alone (4547). While to solve this partial discrepancy is beyond the scope of this study, it has been shown recently that the difference of NIBP and invasive arterial blood pressure is clinically negligible in both adults and children with few exceptions (48,49); NIBP continues to be widely used by ICU physicians (50), and NIBP is proportional to intravascular volume during hemorrhage (12). It is furthermore readily and feasibly available to professionals of all levels of experience and causes few complications (51).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, ample evidence suggesting that non-invasively measured MAP is a better indicator of invasive blood pressure than non-invasive systolic blood pressure alone (4547). While to solve this partial discrepancy is beyond the scope of this study, it has been shown recently that the difference of NIBP and invasive arterial blood pressure is clinically negligible in both adults and children with few exceptions (48,49); NIBP continues to be widely used by ICU physicians (50), and NIBP is proportional to intravascular volume during hemorrhage (12). It is furthermore readily and feasibly available to professionals of all levels of experience and causes few complications (51).…”
Section: Discussionmentioning
confidence: 99%
“…14 Today, intra-arterial blood pressure is often considered to be the gold standard of blood pressure monitoring. 15 Invasive blood pressure monitoring involves direct measurement of arterial pressure by placing a cannula needle in an artery. It provides a more accurate reading of the patient's current blood pressure, but it is generally reserved for critically ill patients where rapid variations in blood pressure are anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a survey of 800 members of the Society of Critical Care Medicine, 73% of respondents reported using NIBP measurement for hypotensive patients and 47% reported using NIBP measurements for patients being treated with a vasopressor. 16 What was unclear in this study was whether clinicians consistently validate the oscillometric method of NIBP measurement by comparing its measurements with auscultatory measurements and whether providers ensured that the size of the blood pressure cuff was accurate for the child's age with the upper extremity positioned level with the right atrium. NIBP measurement is commonly used in the assessment of critically ill children; consistent use of a measurement technique that is based on best evidence is needed in practice to ensure that blood pressure assessment data are accurate.…”
Section: Related Beliefs and Evidencementioning
confidence: 99%
“…However, study results are inconsistent because the research questions vary, the blood pressure measurement techniques are inconsistent, different limbs or body positions are used, the blood pressure parameters assessed (systolic, diastolic, mean) vary, and the statistical procedures used vary, making it difficult to provide a definitive clinical recommendation for acute care practice. 16,[18][19][20] Two studies 14,20 have explored the accuracy of NIBP measurement in critically ill children (Table 1). NIBP Methods.…”
Section: Related Beliefs and Evidencementioning
confidence: 99%
See 1 more Smart Citation